SUCCESSOR-RELATED FACTORS OF EFFECTIVE INTRA-FAMILY SUCCESSION: AN INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS - Hidayati, Aprihatiningrum; Soehadi, Agus W.; Hermawan, Aji; Hartoyo, Hartoyo (Jurnal Aplikasi Manajemen, 2019)
Successor-related factors are among the most discussed topic in family firm succession. The purpose of this study is to explore successor-related factors associated with effective intra-family succession among successors. A total of 10 individuals participated in the study. Using interpretative phenomenological analysis (IPA), four themes emerged from participants' personal statements and experiences: 1) autonomous motivation to take over family firm; 2) intense relationship between predecessor and successor; 3) personality traits; and 4) shared vision. The findings indicate that autonomous motivation to take over the family firm leads to effective intra-family succession since successor's passion aligns with family firms' needs. The intense relationship between predecessor and successor leads to effective intra-family succession in a way an open communication does exist. The smooth transfer of shared vision from predecessor to successor leads to effective intra-family succession. The interesting finding is younger successor differs from elderly successors in perceiving shared vision. Younger successors emphasize on individual motives, while elder successors emphasize on social motives. This work provides deeper insight related to successor-related factors, which leads to effective intra-family succession. In the future, it will be important to explore the potential use of a generational cohort concept in exploring successor-related factor in intra-family succession.